Consolidating a vision on the education of the body. The case of the XII Pan American Congress of Physical Education, Guatemala 1989 (Revista Torreón Universitario, 2022)
From a socio-historical approach with emphasis on the social history of knowledge and experts (Neiburg y Plotkin, 2004; Heilbron, Guilhot, Jeanpierre, 2008; Altamirano, 2013), the following work analyzes the XII Pan American Congress of Physical Education held in Guatemala in 1989. The paper analyzes the event as a space for sociability, knowledge circulation, legitimation of certain experts, influence and power of some international organizations. Taking this into account, the purpose of the article is to examine the knowledge, experts and organizations that validated certain true meanings on how to conceptualize the wide universe of physical culture, physical education and sports (Scharagrodsky, 2011). To carry out the hermeneutical analysis, within the framework of a qualitative methodology, interpretive attention has been focused on various documentary sources, such as memoirs and reports of the congress, the central exhibitions, the general lectures and the memories related to other Pan American congresses. Likewise, a set of semi-structured interviews have been carried out. The analysis has articulated the “text” with the historical conditions of production and interaction of the investigated universe (Fairclough, 2003). Among the conclusions, the congress is identified as a space in which the educational discipline and sports transmitted different meanings about health. In addition, the congress made visible certain international experts and important transnational institutions linked to the heterogeneous field of physical culture.
Keywords: congress; physical education; knowledge; experts; Guatemala